Changes in NAD/ADP-ribose metabolism in rectal cancer - L. Yalcintepe; L. Turker-Sener; A. Sener; G. Yetkin; D. Tiryaki; E. Bermek (Brazilian Journal of Medical and Biological Research, 2005)
The extent of ADP-ribosylation in rectal cancer was compared to that of the corresponding normal rectal tissue. Twenty rectal tissue fragments were collected during surgery from patients diagnosed as having rectal cancer on the basis of pathology results. The levels of ADP-ribosylation in rectum cancer tissue samples (95.9 ± 22.1 nmol/ml) was significantly higher than in normal tissues (11.4 ± 4 nmol/ml). The level of NAD+ glycohydrolase and ADP-ribosyl cyclase activities in rectal cancer and normal tissue samples were measured. Cancer tissues had significantly higher NAD+ glycohydrolase and ADP-ribosyl cyclase activities than the control tissues (43.3 ± 9.1 vs 29.2 ± 5.2 and 6.2 ± 1.6 vs 1.6 ± 0.4 nmol mg-1 min-1). Approximately 75% of the NAD+ concentration was consumed as substrate in rectal cancer, with changes in NAD+/ADP-ribose metabolism being observed. When [14C]-ADP-ribosylated tissue samples were subjected to SDS-PAGE, autoradiographic analysis revealed that several proteins were ADP-ribosylated in rectum tissue. Notably, the radiolabeling of a 113-kDa protein was remarkably greater than that in control tissues. Poly(ADP)-ribosylation of the 113-kDa protein in rectum cancer tissues might be enhanced with its proliferative activity, and poly(ADP)-ribosylation of the same protein in rectum cancer patients might be an indicator of tumor diagnosis.